تحليل الأخطاء النحوية اللغوية عند المحادثة اليومية (دراسة حالية مقارنة) - Roojil Fadillah (IAIN Salatiga, 2017)
This research aims to serve as an Arabic learning reference in Arabic conversation especially for fluent speakers to avoid errors especially in nahwu (syntax). Location selection, therefore, is essential in this research. The researcher chose Islamic boarding schools (pondokpesantren) in Central Java which Arabic proficiency was good, that were PondokPesantren Islam Al-irsyad in Semarang Municipality and Madrasah AliyahNegeri Program Khusus (MANPK) I in Surakarta. This research employed qualitative approach with numerical data to support the conclusion. The method used was descriptive analysis which elaborated all data descriptively in order to obtain thorough and in depth result, as well as to find out more phenomenon and various conversational errors. Therefore, comparative analysis was used. The data were collected through interview, unstructured dialog, and audio recording to gather the empirical data. The research result found out that out of 32 daily conversation errors in each research location, there were 15 syntaxes errors in PondokPesantren Islam Al-Irsyad that were classified into 10 subtopics of syntaxes discussion, while there were 17 syntaxes errors classified into 8 subtopics of syntaxes discussion.